Black Hammer. Volume 8, The end - Lemire, Jeff (Dark Horse Books, 2024)
"In this multi-timeline, world-hopping adventure, we find new stakes, new heroes, and the long-awaited return to Black Hammer farm with the Weber family reuniting and facing many new challenges and villains in Jeff Lemire's biggest event in the Black Hammer series thus far! ... features a sketchbook section.